Estimación de la huella de Carbono mediante el método compuesto por cuentas contables (Mc3), en la línea Ananás comosus, de una empresa del sector hortofrutícola de Colombia (2016)
This research has the general objective to estimate the carbon footprint in the A. comosus line, commonly known as the pineapple, dare adaptation of the method composed of financial accounts (MC3) in two arrays of study in the departments of the Atlantic and Santander, categorized as matrix A and B, respectively. This was guided on the factors and methods published by the intergunamental Panel of Climate Change IPPC and ISO 14040. The methodology involves the application of life-cycle analysis of the A. Comosus stroke, and further analysis of the environmental impacts generated, also, the potential involvement of the compounds of chemicals used in the process of planting is evaluated pineapple, taking into account the categories of Ecoinvent (2010) dare SIMAPRO 8.0 application software. Subsequently, they are left to quantify the incidence of pineapple for the emission of carbon dioxide CO2, this was obtained through the adaptation of MC3 in the Colombian context, throwing as a final conclusion that CO2 generated 43.1 tons in the life cycle of pineapple in the country, where 98% of those are Scope 2 as established by the IPPC.